The Role Of Teachers Of Islamic Religious Education in Motivating Life With Broken Home Family Conditions - Muhammad Syahril; Nurfarida Deliana; Juliana Batubara (Departement of PAI, Universitas Majalengka, 2023)
The study aims to understand the role of teachers of Islamic Religious Education in motivating students with broken home family conditions. The main focus of the research involves the efforts of teachers in providing guidance, motivation, and creating a classroom atmosphere conducive to increasing student learning motivation. Research methods that use qualitative research based field research using phenomenological approaches. With research subjects adalh students with broken home family conditions. Research results show that teachers of Islamic Religious Education actively provide guidance to students by providing guidance, advice, and encouragement to improve the quality of learning. Besides, they build good relationships, communicate, and provide solutions to students' problems both individually and in groups. In an effort to motivate students, teachers of Islamic Religious Education focus on moral and moral cultivation, give advice for students to be more enthusiastic about learning, and create a conducive classroom atmosphere. Teachers are also involved in student discipline handling, giving punishment of an educational nature to create a jera effect. Thus, this research contributes to understanding the role of teachers of Islamic Religious Education in addressing the learning motivation challenge of students with broken home family conditions. The implications of this study are expected to serve as a basis for developing more effective educational strategies to help students overcome the barriers caused by disintegrated family conditions.